PROFIL KINERJA GURU MADRASAH TSANAWIYAH NEGERI 3 Pekanbaru - Rina Darmayanti; Sumardi Sumardi; Nurpit Junus (Universitas Riau, 2021)
This research is descriptive qualitative research. The technique of data collection was done through observation, interview and documentation.This research was conducted at MTs Negeri 3 Pekanbaru, the object of the research is to look at the profile of professional teacher performance.Research aims (1) to analyze the performance of teacher professional learning activities in drawing up the programme in MTs Negeri 3 Pekanbaru, (2) to analyze the performance of professional teachers in carrying out the activities of learning at MTs Negeri 3 Pekanbaru and (3) to analyze the performance of professional teachers in assessing any late learners learning in MTs Negeri 3 Pekanbaru.The respondents of the research was all the teachers who have been certified in MTs Negeri 3 Pekanbaru is 42 professional teachers.The results obtained from this research are (1) there are a number of professional teachers make mistakes in formulating indicators of learning and learning strategies that are not in accordance with the contents of the learning and also in the writing of time allocation in the syllabus found some errors that are not in compliance with the allocation of time each function, (2) Found a few professional teachers using model/approach to learning that is not in accordance with the the learning step (3) In giving assesment there are still few professional teachers in MTs Negeri 3 Pekanbaru use student worksheet question bank not assess students understanding in accordance with the new material is submitted.It can be seen from the annex to the assessment that is in the RPP does not correspond to the given exercise teacher to students.